A Case of Posterior Reversible Encephalopathy Syndrome Associated with Gilenya® (Fingolimod) Treatment for Multiple Sclerosis - Lindå, Hans; von Heijne, Anders (Frontiers in Neurology, 2015)
We describe Posterior Reversible Encephalopathy Syndrome (PRES) in a woman with Multiple Sclerosis (MS) treated with Gilenya® (Fingolimod). The first symptoms appeared after 21 months of fingolimod treatment. She experienced headache, altered mental status, cognitive deficits, seizures and visual disturbances. Not at any time during the course of the disease could any signs of infection or rheumatic disorder be detected. Test for anti-neuronal antibodies was also negative. Her bloodpressure was normal. MRI showed widespread cortical and subcortical changes with some mass-effect in the temporo-occipital-parietal lobes in the left hemisphere. Contrast enhancement was seen in the leptomeninges and, in addition, there were no areas with restricted diffusion and no signs of hemorrhage. Her condition deteriorated until fingolimod was discontinued. Slowly her condition improved and after 8 months, the only symptoms that remained were two small, non-corresponding, right inferior scotomas. We believe that all symptoms, the clinical course and the MRI findings in this case can all be explained by considering PRES, a probably rare, but serious, side-effect of fingolimod treatment.